QUANTITATIVE RISK ASSESSMENT OF THE AH-140 SHIP-BUILDING PROJECT AT PT. PAL INDONESIA TO SUPPORT THE DUTIES OF THE INDONESIAN NAVY - Simon Fuad Sonda; Budi Santoso; Ahmadi Ahmadi; Richard Martin (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
The AH-140 Shipbuilding project is a challenge for PT.PAL as part of the Indonesian Defense Industry Holding under PT. LEN Industry is under a situation of uncertainty, which will bring up both positive and negative risks. Negative risks that can cause project delays should be mitigated to prevent delays. This thesis has the aim of knowing the interaction between risks and obtaining mitigation recommendations for the implementation of the AH-140 Shipbuilding project. Bayesian Network is used to determine the level of project risk interaction, as well as to model scenarios by providing certainty on the risks that have an effect. AHP is used to assess the chance of occurrence at Independence risk and ANP is used to assess opportunities from Dependence risk. In the study, it was found that there were 22 risks. risk (E14) Quality of work, risk (E20) Cost overrun, and risk (E7) material shortage. The influence of risk variables that have the potential to occur in the AH-140 Shipbuilding project, causing potential delays in ship launching at a Low-risk level with actual conditions of 43%, Medium risk Level with actual conditions of 31%, and High-risk level with actual conditions of 26%. This is influenced by the risk (E14) of the quality of work, the risk (E20) of cost overrun, and the risk (E7) of material shortages. So that get some recommendations in response to risks that have the potential to occur. Keywords: Project Risk Management, Bayesian Network, AHP, ANP.